Implementasi Metode Bayesian Network untuk Diagnosis Penyakit Telinga Hidung dan Tenggorokan (THT) - Mustofa Robbani; Nurul Hidayat; Budi Darma Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Ear nose and throat disease one of the harmful disease, lack of hygiene and the difficulty in keeping the communities to diagnose due to the similarity of symptoms and diseases of the ear nose and throat, in addition to the conditions in the village It is located far from hospitals - major hospitals lead to sluggish handling of the ear nose and throat. Allow the occurrence of the disease is worse so detrimental to society or to patients themselves. Then it takes a software which can help the community or patient so expect that software can help communities to diagnose diseases of the ear nose and throat. Then the software was made using Bayesian Network methods, and to facilitate operation then made software with Android-based operating system. This software has the input based on the symptoms - symptoms of the disease that is selected by the user and is processed by methods of Bayesian Network so as to generate output in the form of disease and suffered from the results of testing the accuracy of data 42 It brings the accuracy of 93.75%.